The excursion - Brooke, Frances, 1724?-1789 (Eighteenth-century novels by women., 1997)
Frances Brooke (1724-1789), journalist, translator, playwright, novelist, and even co-manager of a theater, was described as ""perhaps the first female novel-writer who attained a perfect purity and polish of style."" Today, Brooke is known primarily for The History of Emily Montague, one of the earliest novels about Canada, where she lived for a number of years. But it is her third novel, The Excursion, that is an important example of the fashionable and popular English novels of the late 1770s. Written for the very audience it portrays, this novel introduces the heroine, Maria Villiers, to